Prevalence of Cardiovascular Risk Factors with Aging: A Study in a Biologically Isolated Group of North East India - Bordoloi, Trinayani; Kapoor, A.K. (Asian Journal of Biological and Life Sciences, 2013)
Cardiovascular diseases become increasingly common with advancing age. As a person gets older, the heart undergoes subtle physiologic changes. The present study was conducted in a biologically isolated group viz. Kalita, a caste population of Assam, North East India to find out the ageing trend in cardiovascular risk factors and its association with anthropometric adiposity indices. The cross sectional study included 482 adult females aged 20¬49 years. The subjects were divided into three different age groups to study the ageing trend. In the present study cardiovascular risk increases significantly with age. Positive correlation of waist circumference and waist height ratio with blood pressure indicates regional obesity to be a risk factor for cardiovascular health.